Strengthening environmental soft law commitments with the principle of pacta sunt servanda - (:unkn) unknown (My University, 2022)
The principle of pacta sunt servanda is a principle applied in both Roman law and international law. The significant difference in practice between these two disciplines is based on the judicial field in Roman law and the normative field in international law. Our study deals with the Roman law principle of pacta sunt servanda in the first chapter, and the international law principle of pacta sunt servanda in the second chapter. Theoretical discussions on ensuring the binding ground of the commitments are covered in the third chapter. While examining the different approaches, our study relates pactums that do not have a normative value in Roman law, but that are judicially recognized, with today’s environmental soft law commitments. In the nuisance-based environmental law approach, the basis for judicial consideration is presented as environmental exigencies. Thus, it is aimed to lay the groundwork for judicially binding environmental soft law commitments.

Pacta sunt servanda ilkesi, hem Roma hukukunda hem de uluslararası hukukta uygulanmış bir ilkedir. Bu iki disiplin arasındaki belirgin uygulama farkı, Roma hukukunda yargısal, uluslararası hukukta ise normatif alana ilişkin olmasına dayanır. Çalışmamız ilk bölümde Roma hukukunda pacta sunt servanda ilkesini, ikinci bölümde ise uluslararası hukukta pacta sunt servanda ilkesini işlemektedir. Üçüncü bölümde taahütlerin bağlayıcılığının temininde teorik tartışmalar işlenmiştir. Çalışmamız yaklaşım farklılıklarını incelerken Roma hukukunda normatif değeri bulunmayıp yargısal olarak tanınan pactumlar ile günümüzdeki çevresel esnek hukuk taahhütleriyle ilişkilendirmektedir. Mesele odaklı çevre hukuku yaklaşımında yargıçların nazarı itibara alacakları dayanak, çevresel aciliyetler olarak sunulmuştur. Böylece çevresel esnek hukuk taahhütlerinin yargısal olarak bağlayıcılığı için bir zemin hazırlanması amaçlanmaktadır.
Çevresel esnek hukuk taahhütlerinin pacta sunt servanda ilkesiyle güçlendirilmesi
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Devletler Umumi Hukuku; Social Sciences and Humanities; Law; International Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Hukuk; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Pacta Sunt Servanda; Environmental Soft Law; Roman Law; International Law; Logic; Çevresel Esnek Hukuk; Roma Hukuku; Uluslararası Hukuk; Mantık